Is it Good to Make Happy People? - Rachels, Stuart (Bioethics, 1998)
Would it be good, other things being equal, for additional people to exist whose lives would be worth living? I examine and reject several arguments for the answer that it would not be good; then I offer opposing arguments that I believe are more successful. Thus, I agree with utilitarians who say that it is better for there to be more happy people. Next I argue for the stronger claim that the happiness of potential people is as important as that of adults. Potential quality of life, then, matters in a host of bioethical issues: abortion, commercial surrogacy, the treatment of defective newborns, and so on. What is the practical upshot of all this? I reject the idea that we must do whatever is necessary to prolong life worth living. But I also reject the view that the side-effects of overpopulation always outweigh the value of realizing potential happiness. So I advocate a middle position, which I do not identify precisely. Even from this middle position, however, potential happiness is more important than is commonly assumed in bioethics.